1994
DOI: 10.1144/pygs.50.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Lithostratigraphical subdivision of the Triassic Sherwood Sandstone Group in west Cumbria

Abstract: SUMMARY The subdivisions of the Sherwood Sandstone Group, previously recognized on geophysical and lithological criteria in boreholes offshore in the East Irish Sea Basin, can be identified in the onshore exposures and boreholes of west Cumbria. The term St Bees Sandstone Formation is here restricted to the lower, fluvial, fine-grained sandstone, with claystone and siltstone partings, exposed around St Bees. This formation is sharply overlain by softer and coarser grained, aeolian and subordinate flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 18 publications
4
19
0
Order By: Relevance
“…Essentially the same lithostratigraphical units were recognised onshore in west Cumbria by Barnes et al (1994) (see also Akhurst et al 1997; Survey 1999) from the study of outcrops and by the examination of the more complete sections provided by the several kilometres of core from boreholes drilled around Sellafield (Michie & Bowden 1994). However, some different names and a different hierarchy were proposed, principally because the Calder Sandstone Formation in this area was noticeably coarser grained than either the St Bees or the Ormskirk Sandstone formations, or its offshore equivalent, the Calder Sandstone Member (Tables 2, 3).…”
Section: East Irish Sea and Solway Firth Basins And West Cumbriamentioning
confidence: 74%
See 4 more Smart Citations
“…Essentially the same lithostratigraphical units were recognised onshore in west Cumbria by Barnes et al (1994) (see also Akhurst et al 1997; Survey 1999) from the study of outcrops and by the examination of the more complete sections provided by the several kilometres of core from boreholes drilled around Sellafield (Michie & Bowden 1994). However, some different names and a different hierarchy were proposed, principally because the Calder Sandstone Formation in this area was noticeably coarser grained than either the St Bees or the Ormskirk Sandstone formations, or its offshore equivalent, the Calder Sandstone Member (Tables 2, 3).…”
Section: East Irish Sea and Solway Firth Basins And West Cumbriamentioning
confidence: 74%
“…Barnes et al (1994) (also Jackson et al 1995;Jackson & Johnson 1996) suggested that these boundaries are disconformities, the uppermost corresponding to the Hardegsen Disconformity. These observations contradicted the previous investigations of Eastwood et al (1931) and Trotter et al (1937) who concluded that there were no major breaks in the sequence and that the aeolian beds are a local lithofacies of the fluvial rocks and cannot be separately mapped at surface.…”
Section: East Irish Sea and Solway Firth Basins And West Cumbriamentioning
confidence: 98%
See 3 more Smart Citations